The ever unfolding story of cAMP signalling in trypanosomatids: vive la difference! - Daniel Nii Aryee Tagoe; Daniel Nii Aryee Tagoe; Daniel Nii Aryee Tagoe; Titilola D. Kalejaiye; Harry P. De Koning (Frontiers Media S.A., 2015)
Kinetoplastids are unicellular, eukaryotic, flagellated protozoans containing the eponymous kinetoplast. Within this order, the family of trypanosomatids are responsible for some of the most serious human diseases, including Chagas disease (Trypanosoma cruzi), sleeping sickness (T. brucei spp.) and leishmaniasis (Leishmania spp). Although cAMP is produced during the life cycle stages of these parasites, its signalling pathways are very different from those of mammals. The absence of G-protein-coupled recep¬tors, the presence of structurally different adenylyl cyclases, the paucity of known cAMP effector proteins and the stringent need for regulation of cAMP in the small kinetoplastid cells all suggest a significantly different biochemical pathway and likely cell biology. However, each of the main kinetoplastid parasites express four class 1-type cyclic nucleotide-specific phosphodiesterases (PDEA-D), which have highly similar catalytic domains to that of human PDEs. To date, only TbrPDEB, expressed as two slightly different isoforms TbrPDEB1 and B2, has been found to be essential when ablated. Although the genomes contain reasonably well con¬served genes for catalytic and regulatory domains of pro¬tein kinase A, these have been shown to have varied structural and functional roles in the different species. Recent discovery of a role of cAMP/AMP metabolism in a quorum-sensing signalling pathway in T. brucei, and the identification of downstream cAMP Response Proteins (CARPs) whose expression levels correlate with sensitivity to PDE inhibitors, suggests a complex signalling cascade. The interplay between the roles of these novel CARPs and the quorum-sensing signalling pathway on cell division and differentiation makes for intriguing cell biology and a new paradigm in cAMP signal transduction, as well as potential targets for trypanosomatid-specific cAMP pathway-based therapeutics.